2014
DOI: 10.3329/jbau.v11i2.19899
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical attributes and correlation among grain quality traits of some exotic aromatic rice lines

Abstract: Forty three rice genotypes were used to evaluate their aroma detection through sensory test. Aroma was detected by 1.7% KOH as a sensory test. Thirteen rice genotypes were detected having strong aroma; ten had moderate aroma; fifteen had slight aroma and five had no aroma. In case of grain shape study, 37 genotypes were evaluated as slender and six as medium. In this study, grain aroma had significant and positive association with grain length width ratio; significant and negative association with grain width,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Rice grain quality plays a vital role in consumer satisfaction since rice is mainly consumed as whole grain, especially in Asia (Seraj, Hassan, Begum, & Sarker, 2013). Likewise, grain quality traits define the market value and have an important role in the release of new varieties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rice grain quality plays a vital role in consumer satisfaction since rice is mainly consumed as whole grain, especially in Asia (Seraj, Hassan, Begum, & Sarker, 2013). Likewise, grain quality traits define the market value and have an important role in the release of new varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Rice quality traits include milling recovery, physical appearance, cooking and eating qualities, and nutritional value (Hori, Suzuki, Iijima, & Ebana, 2016;Koutroubas, Mazzini, Pons, & Ntanos, 2004). Gel consistency (GC), amylose content (AC), alkali spreading value (GT), and protein content (PC) of noodle rice have specific importance for human health (Seraj et al, 2013). Similarly, amylose content is generally used to examine the eating and cooking quality of noodle rice, which is why high amylose content is preferred for superior eating and cooking quality of noodle rice (Ahmed, Qazi, Li, & Ullah, 2016;Fahad et al, 2019;Gao, Lukow, & Grant, 2012;Vithu & Moses, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It was positively correlated with length-to-breadth ratio (r = 0.75**) and thousand kernel weight (r= 0.65***) which indicates that the more slender the rice grain, the longer the grain and the greater the weight. The correlation between kernel length with length-to-breadth ratio was also found positive in the experiments of Odenigbo et al 2014, Rafii et al (2014) and Seraj et al (2013) on the study of correlation of grain quality traits in aromatic rice lines. A study by Mia et al (2012) on aromatic fine grain rice showed that the grain weight increases with kernel length that agrees with the present finding.…”
Section: Correlation Among Physical Characteristics and Nutritional Cmentioning
confidence: 60%